PENGARUH PELAKSANAAN PENILAIAN UNJUK KERJA TERHADAP KEMAMPUAN PSIKOMOTORIK SISWA PADA MATA PELAJARAN PAI DI SMA N 2 TELUK KUANTAN - Isasli Isasli; Sopiatun Nahwiyah; Sarmidin Sarmidin (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
This thesis Talks about the influence of the implementation of the work of psychomotor students in schools 2 teluk kuantan . This study aims to know the whereabouts of work and how much influence on psychomotor students in schools 2 teluk kuantan.The methodology consist of a method of observation ,tests and documentation. Respondent in this research was students XI .There are two variables assessment on the research work and psychomotor students .The data analysis techniques used technique gave pearson correlation with the product moment. After the calculation is done, the writer draws conclusions, namely, "The statement tested is valid in terms of salvation because t hitung ≥ t table is the value of t (table) 14.836. The measuring instrument used in this study is reliable reliability. The results of a simple linear regression constant of 1,286 means that if the independent variable X (implementation of he work) has a value of 0, then the dependent variable Y (psycomotor student) is 1,286. Where it was done calculations that the value of a correlation coefficient dikeahui 0,982 . Because of the approaching 1 so it can be concluded that the relationship between were working with psychomotor students are very closely.